Major cellular events in peripheral nerve regeneration: A brief overview - M, Naidu; P, David (IIUM Medical Journal Malaysia, 2009)
Injury to a peripheral nerve leads to degeneration of the segment distal to the site of lesion, a process referred to as Wallerian degeneration. During Wallerian degeneration, axons and myelin sheaths undergo degeneration and are phagocytosed by macrophages and Schwann cells. The Schwann cells proliferate and the endoneurial tubes persist, together the whole structure is known as the band of Büngner. Within few hours, the damaged axons in the proximal stump initiate a regeneration response, with formation of new growth cones. During Wallerian degeneration, neurotrophins, neural cell adhesion molecules, cytokines and other soluble factors are upregulated to facilitate regeneration. The recovery of the target in mammals is often variable, but almost never complete. In humans, scar tissue forms at the site of lesion and this often results in poor recovery of the target. The major events underlying this regenerative process is highlighted and discussed in this review.